-(3y+1)-(-2y-4)=-1

Simple and best practice solution for -(3y+1)-(-2y-4)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(3y+1)-(-2y-4)=-1 equation:


Simplifying
-1(3y + 1) + -1(-2y + -4) = -1

Reorder the terms:
-1(1 + 3y) + -1(-2y + -4) = -1
(1 * -1 + 3y * -1) + -1(-2y + -4) = -1
(-1 + -3y) + -1(-2y + -4) = -1

Reorder the terms:
-1 + -3y + -1(-4 + -2y) = -1
-1 + -3y + (-4 * -1 + -2y * -1) = -1
-1 + -3y + (4 + 2y) = -1

Reorder the terms:
-1 + 4 + -3y + 2y = -1

Combine like terms: -1 + 4 = 3
3 + -3y + 2y = -1

Combine like terms: -3y + 2y = -1y
3 + -1y = -1

Solving
3 + -1y = -1

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -1y = -1 + -3

Combine like terms: 3 + -3 = 0
0 + -1y = -1 + -3
-1y = -1 + -3

Combine like terms: -1 + -3 = -4
-1y = -4

Divide each side by '-1'.
y = 4

Simplifying
y = 4

See similar equations:

| 3(x-2)(x+1)=0 | | -2y+6=20 | | 4z-7=5(5z-3) | | (5b-1)(6b-3)= | | 2x+20=304 | | -6x-(9y+(5x-(-2y-b))-(2b+a))= | | 2t^2-20t=0 | | 2(3v-1)+7v+7=5(v-6)+3v | | 304=s+20 | | 304=s+20w | | (4+w)(5w-8)=0 | | 30+9y=16y | | 5(w+2)-6(w+4)=0 | | (-6x-z)-(3y+(7x-(3z+8y+x)))= | | (5w+6)(5w-6)= | | -X+2x^2=0 | | -(8y+2)-(-7y-5)=-1 | | B=b+2a+3c | | 8(3x-8)=2(12x+7) | | (18y^2-12xy)-(6y^2+xy-a)= | | 3+3s-2=8s+5-3s | | 4(3w+1)+4v=4(v-6)-2v | | 6t+8t=84 | | 9ln(4x)=54 | | 6ay^3+5ay^2-4ay= | | (2.25c-9.28b+3.82a)-(-3.92a-1.72b-8.33c)= | | 2p=5p+9 | | 90=2x*3x+1+5*5 | | -8(3b+2)+(25b-9)=0 | | (23y^2+4y^3-12)-(11y^3-8y^2+y)= | | 3.1q-2.2-5.3q=-3.2q-1.2 | | 9+x^2=0 |

Equations solver categories